Design of a LNA and a Gilbert Cell Mixer MMICs with a GaAs PHEMT technology - Martins, E. [UNESP]; Gomes, M. V G [UNESP]; Bastida, E. M. [UNESP]; Swart, J. W. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 1999)
The design of a Gilbert Cell Mixer and a low noise amplifier (LNA), using GaAs PHEMT technology is presented. The compatibility is shown for co-integration of both block on the same chip, to form a high performance 1.9 GHz receiver front-end. The designed LNA shows 9.23 dB gain and 2.01 dB noise figure (NF). The mixer is designed to operate at RF=1.9 GHz, LO=2.0 GHz and IF=100 MHz with a gain of 14.3 dB and single sideband noise figure (SSB NF) of 9.6 dB. The mixer presents a bandwith of 8 GHz.
Keywords: Front end receivers; Gilbert cell mixers; Low noise amplifiers; Pseudomorphic high electron mobility transistors; Amplifiers (electronic); Buffer circuits; Computer simulation; Electric network topology; High electron mobility transistors; Mixer circuits; Monolithic microwave integrated circuits; Semiconducting gallium arsenide; Signal receivers; Integrated circuit layout